Ultrasensitive and Highly Stretchable Multifunctional Strain Sensors with Timbre‐Recognition Ability Based on Vertical Graphene. (9th October 2019) - Deng, Caihao; Gao, Peixiong; Lan, Linfeng; He, Penghui; Zhao, Xin; Zheng, Wei; Chen, Wangshou; Zhong, Xizhou; Wu, Yunhui; Liu, Lan; Peng, Junbiao; Cao, Yong
Abstract: Stretchable/wearable strain sensors are attracting growing interest due to their broad applications in physical and physiological measurements. However, the development of a multifunctional highly stretchable sensor satisfying the requirements of ultrahigh sensitivity (able to distinguish sound frequency) remains a challenge. An ultrasensitive and highly stretchable multifunctional strain sensor with timbre‐recognition ability based on high‐crack‐density vertical graphene (VGr) is fabricated using an ultrasonic peeling (UP) method. It can distinguish frequencies of sounds higher than 2500 Hz. Detailed microscopic examinations reveal that their ultrahigh sensitivity stems from the formation of high‐density nanocracks in the graphitic base layer, which is bridged by the top branched VGr nanowalls. These nanocracks cut the VGr film into a large number of nanopieces, which increase the natural frequency of the sensors, enabling the sensors to distinguish the sound frequency. Demonstrations are presented to highlight the sensors' potential as wearable devices for human physiological signal and timbre detections. This is the first multifunctional highly stretchable strain sensor with timbre‐recognition ability. Abstract : An ultrasensitive and highly stretchable multifunctional strain sensor with timbre‐recognition ability based on high‐crack‐density vertical graphene is fabricated using an ultrasonic peeling method. The strain sensor has a gauge factor of 22 000 at a strain of 100%, and can distinguish frequencies of sounds higher than 2500 Hz.